Analisis Penerapan Sistem Manajemen Keselamatan Konstruksi Pada Proyek Pembangunan Kantor Bappedalitbang Kota Samarinda - Zulkifli; Effendi Arifin, Benny Mochtar; Tukimun (Universitas Veteran Bangun Nusantara, 2025)
Construction work is a sector with a high risk of workplace accidents, requiring a structured and continuous implementation of the Occupational Safety and Health Management System (SMK3). This study aims to analyze the implementation of SMK3 in the development and rehabilitation project of the Bappedalitbang Office Building in Samarinda City, to assess how effectively occupational safety and health aspects are being applied. A qualitative method was used, with data collection techniques including direct observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, verification, and drawing conclusions. The results show that the availability of occupational safety facilities in the project has met the established standards, achieving 83%, which is categorized as “good” according to the Minister of Public Works Regulation No. 9 of 2008. The implementation of SMK3 also demonstrates a strong commitment from the project management, with an implementation score of 85.6%, indicating relatively optimal management of safety and health. However, there are still several inhibiting factors, such as the lack of education for workers, suboptimal use of personal protective equipment (PPE), and weak enforcement of safety regulations on-site. Based on these findings, continuous improvement is needed in the areas of training, safety audits, and routine monitoring to enhance the overall quality of SMK3 implementation. This research is expected to serve as a reference for formulating strategies to improve workplace safety in construction projects, both in the public and private sectors.